Sustainable Models for Genetic Improvement of Livestock - Marshall, Karen (2021)
Presentation by Karen Marshall, livestock genetics flagship leader, on how the theory of change of the flagship helped transform the team’s approach to genetics research. This presentation was delivered as part of the golden eggs session of the final celebration and closing meeting of the CGIAR Research Program on Livestock in Oct 2021.